HIRSCHSPRUNG’S DISEASE IN AN ADULT: A CASE REPORT - Shitta, AH (J West Afr Coll Surg, 2014)
Hirschsprung’s disease in the adolescents and adults is not a common diagnosis in our environment. However this may be as a result of misdiagnosis or late presentation as is the case with other causes of recurrent constipation in older age groups. We present a case of a 19-year old male who presented with recurrent episodes of constipation from infancy with none requiring any intervention except for the index presentation that lasted for 3 weeks with associated progressive abdominal distension. Diagnosis was made with a barium enema and full thickness rectal biopsy. He had staged procedures with an initial divided colostomy thereafter followed by a definitive Souave endorectal pull-through with a good short-term outcome.